Intact painful sensation but enhanced non-painful sensation in individuals with autistic traits - Qian, Huiling; Shao, Min; Wei, Zilong; Zhang, Yudie; Liu, Shuqin; Chen, Lu; Meng, Jing (Frontiers in Psychiatry, 2024)
Somatosensory abnormalities are commonly recognized as diagnostic criteria in autism spectrum disorder (ASD), and may also exist in individuals with autistic traits. The present research included two studies to explore the painful and non-painful sensation and their cognitive-neurological mechanisms of individuals with autistic traits. Study 1 included 358 participants to assess the relationship between autistic traits and pain/non-pain sensitivities using questionnaires: the Autism Spectrum Quotient (AQ), the Pain Sensitivity Questionnaire, and the Highly Sensitive Person Scale, respectively. Study 1 found that autistic traits were positively correlated with non-pain sensitivity, but not associated with pain sensitivity. Study 2 recruited 1,167 participants whose autistic traits were assessed using the AQ. Subsequently, thirty-three participants who scored within the top 10 % and bottom 10 % on the AQ were selected into High-AQ and Low-AQ groups, respectively, to explore the cognitive-neural responses of individuals with autistic traits to both painful and non-painful stimuli with event-related potential (ERP) technology. Results of Study 2 showed that the High-AQ group showed higher intensity ratings, more negative emotional reactions, and larger N1 amplitudes than the Low-AQ group to the non-painful stimuli, but no difference of response to the painful stimuli was found between High-AQ and Low-AQ groups. These findings suggest that individuals with autistic traits may experience enhanced non-painful sensation but intact painful sensation.